Rhythms of academic life personal accounts of careers in academia (Foundations for Organizational Science, 1996)
Offering support, guidance, and advice for those contemplating or already involved in academic careers, Rhythms of Academic Life is a comprehensive work that surveys important topics relevant to the world of academia, such as publishing, research, teaching, pedagogy, teamwork, sabbaticals, and tenure. Written by a diverse group of scholars, this collection provides rich, personal, sometimes poignant, and often humorous accounts of both the common and the unique journeys taken throughout an academic lifetime. The contributors describe the experiences of scholars in different roles and transition points and supply a set of guidelines that will help others make informed choices. This one-of-a-kind volume makes it possible to enter into an academic career well-prepared and familiarizes the reader with the academic work climate.